Imágenes de Safo en la literatura española (III): la segunda mitad del siglo XIX - Barrero Pérez, Óscar (Dicenda. Estudios de lengua y literatura españolas, 2008)
In this article is analysed the view presented by Spanish Literature of the second half of XIX century about Greek poet Safo. The legendary bias is presented in a teather text by Víctor Balaguer and in another one by Pascual de Sanjuán. Menéndez Pelayo y Valera's cultural formation encourage them to be also interested in Safo's figure, although it wasn't be until Eighty years, since the apparition of a Fernández Merino's documented book, when History begans to occupy the place of the legend, as is yet demostrated in Castelar's work. That is the beginning point of a review of Safo's image, image since then more nearest to the historical truth than to its fascinanting legend.